Multivariate analysis of medication adherence among outpatients with stable coronary artery disease - Fitilev, S. B.; Vozzhaev, A. V.; Kliuev, D. A.; Shkrebniova, I. I. (Kachestvennai͡a︡ klinicheskai͡a︡ praktika, 2022)
Introduction. The results of local studies indicated that medication adherence of coronary outpatients is low (not more than 60 %). The search for significant predictors of adherence to recommended treatment might allow tailoring specific strategies to control adherence for further optimization of the pharmacotherapy of coronary artery disease (CAD) in routine primary care practice. Aim. To determine the factors associated with medication adherence in outpatients with stable CAD. Methods. This paper describes the results of the fragment of randomized controlled study of the effects of Pharmacy Care Program on medication adherence of coronary outpatients, that was conducted in 2019-2020 in one of the primary care clinics of Moscow. 123 subjects with stable CAD were included in line with the pre-specified criteria. Demography, social status, medical history, pharmacotherapy, healthcare burden data were registered. Medication adherence was measured by validated questionnaire MMAS-8 (8-item Morisky Medication Adherence Scale). The analysis of predictors of adherence was performed by linear regression. Results. Simple regression analysis revealed the list of parameters, that showed statistically significant (or as statistical trend) association with medication adherence of coronary patients in univariate models. The level of medication adherence was associated with patient’s having a partner or caregiver (p=0,002), higher education (p=0,009), additional medicinal maintenance (p=0,006). Medication adherence did not depend on medical history and pharmacotherapy characteristics, but the association of high values of low-density lipoproteins cholesterol (LDL-C) (p=0,001) with suboptimal adherence was demonstrated. Good medication adherence was associated with more frequent visits to general practitioner (p=0,036) and (as statistical trend) to cardiologist (p=0,093). The multivariate regression analysis revealed two positive independent predictors of medication adherence - patient’s having a partner or caregiver (р=0,015) and regular visits to cardiologist (р=0,025). Also, the negative association was confirmed for high LDL-C (р=0,002). Conclusion. Patient’s having a partner or caregiver and regular visits to cardiologist were revealed as independent predictors of good medication adherence of coronary outpatients. Subjects with suboptimal adherence had higher LDL-C.